2013
DOI: 10.1039/c3ta11265a
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study of electron and hole transport in pure and doped MnO and MnO:ZnO alloy

Abstract: Rationally engineering photocatalytic devices that power water splitting or CO 2 reduction reactions requires identifying economical materials that efficiently absorb sunlight and have suitable band edge placements. Recent theoretical investigations have predicted that a 1 : 1 alloy of MnO and ZnO meets these criteria. However, poor hole conductivity in undoped MnO:ZnO alloys (with up to 10% ZnO) severely limits this material's utility in electronic devices, and its electron conductivity has not yet been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…The feature of a dispersive conduction band was also recently found for ternary Mn(II) oxides [31]. Thus, electron transport in MnO-ZnO alloys should be described as large-polaron band conduction and not as small-polaron hopping conduction [13]. For hole carriers, the transport mechanism depends on the structure: In the octahedral coordination environment of RS MnO, the small-polaron formation is exothermic, i.e., the self-trapping energy E ST for the process Mn þII þ h þ → Mn þIII is negative (here, h þ denotes a positively charged hole carrier at the VBM).…”
Section: Transport Properties and Dopingmentioning
confidence: 96%
See 2 more Smart Citations
“…The feature of a dispersive conduction band was also recently found for ternary Mn(II) oxides [31]. Thus, electron transport in MnO-ZnO alloys should be described as large-polaron band conduction and not as small-polaron hopping conduction [13]. For hole carriers, the transport mechanism depends on the structure: In the octahedral coordination environment of RS MnO, the small-polaron formation is exothermic, i.e., the self-trapping energy E ST for the process Mn þII þ h þ → Mn þIII is negative (here, h þ denotes a positively charged hole carrier at the VBM).…”
Section: Transport Properties and Dopingmentioning
confidence: 96%
“…Small-polaron hopping transport is generally characterized by low mobilities, usually assumed to be μ ≪ 0.1 cm 2 =Vs ("Bosman-van Daal limit") [4]. A recent study on the polaron hopping transport in RS structure MnO-ZnO alloys [13] found sizable energy barriers around 0.5 eV, suggesting hole mobilities below 10 −6 cm 2 =Vs at room temperature. In the context of solar absorber materials, an important additional implication is that the small polaron creates a deep defect state inside the band gap that acts as a detrimental recombination center [8].…”
Section: Transport Properties and Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…One model of solvation involves adding water layers with water molecules explicitly bound to the surface and water molecules hydrogenbonded to each other in multilayered structures. Y, Al, or Gd) [32] might reveal a dopant that provides the optimal relative binding strengths that minimize the overpotential. [28] Similarly, the effects of solvation on the remaining intermediates (*O and *OOH) need to be determined.…”
Section: Model Limitations and Implications For Photocatalysismentioning
confidence: 99%
“…[21,22,31] Evaluating the scaling relationships for the reaction intermediates on MnO:ZnO in the presence of recently proposed n-dopants (e.g. Y, Al, or Gd) [32] might reveal a dopant that provides the optimal relative binding strengths that minimize the overpotential. However, previous work on doping hematite did not find doping to appreciably break the linear scaling relationships.…”
Section: Model Limitations and Implications For Photocatalysismentioning
confidence: 99%